Impact of Dietary Diversification on the Prognostic Inflammatory and Nutritional Index in School-Age Children in the Nawa Region (Côte d’Ivoire) - Jean Maurel, Allico Mousso; Edith, Agbo Adouko; Laurent, Séri Kipré; Lydie, Boyvin; Christophe, Kouamé; Félix, Yapi Houphouët; Joseph, Djaman Allico (International Journal of Child Health and Nutrition, 2021)
The objective of this work was to study the impact of food diversification based on sweet potato, soybean, and cowpea on the prognostic inflammatory and nutritional index (PINI) in school-aged children in the Nawa region. This study took place from October 2017 to May 2018 among 240 pupils aged 6 to 12, divided into four groups of 60. Four types of meals were proposed: rice with tomato soup and fish (group 1), sweet potato porridge enriched with green soybeans (group 2), sweet potato porridge enriched with white cowpea (group 3), or sweet potato porridge accompanied by white cowpea with green soybeans (group 4). There were three blood samples: before eating meals (phase 0), the end of the first trimester (phase 1), and the end of the second trimester (phase 2). Blood assay for C-reactive protein (CRP), orosomucoid, albumin, and prealbumin was performed using COBAS c311 analyzer. PINI was calculated. Groups 3 and 4 showed a slight increase in albumin values (42.24 ± 0.95 g/L and 41.51 ± 1.71 g/L, respectively) compared to group 1. CRP decreased from phase 1 for group 1 (2.06 ± 0.26 mg/L) and group 4 (2.38 ± 0.36 mg/L). Orosomucoid increased insignificantly (p > 0.05) in group 3 (0.74 ± 0.04 g/L) and group 4 (0.71 ± 0.04 g/L). PINI was reduced by 0.37 (group 1), 0.36 (group 2), 0.46 (group 3) and 0.44 (group 4). Food diversification based on sweet potato and white cowpea has a positive impact on PINI in more than 80% of pupils.